Experimental Pseudomonas aeruginosa Keratitis in Interleukin-10 Gene Knockout Mice - Cole, Nerida (American Society for Microbiology, 2003)
Pseudomonas aeruginosa keratitis is one of the most destructive diseases of the cornea. The host response to this infection is critical to the outcome. The cytokine interleukin-10 (IL-10) is thought to play an important role in modulating excessive inflammation and antimicrobial defenses. We have found that in IL-10(−/−) mice there is a significant decrease in bacterial load in corneas at 7 days postchallenge with P. aeruginosa. This decrease was accompanied by a reduction in neutrophil numbers in the cornea and changes in cytokine levels compared to those of wild-type mice. A characteristic increase in neovascularization in the cornea was found in the IL-10(−/−) mice. This increased angiogenesis correlated with an increased expression of KC, whereas the kinetics of macrophage inflammatory peptide 2 expression correlated with neutrophil numbers. This finding suggests that KC may play a role in corneal angiogenesis. The source of IL-10 in mouse corneas was identified as a subpopulation of infiltrating cells and keratocytes. This study demonstrates that IL-10 plays an important role in regulating the balance of inflammatory mediators during P. aeruginosa infection of the cornea.